Automatic : Changing the Way America Saves. - Gale, William G. (Brookings Institution Press, 2011)
Automatic offers an innovative new way to think about how Americans can save for retirement. Over the past quarter century, America?s pension system has shifted away from defined benefit plans and toward defined contribution savings programs such as 401(k)s and IRAs. There is much to be done to improve the defined contribution system. Many workers fail to participate and those who do often contribute too little, invest the funds poorly, and are not adequately prepared to manage funds while in retirement. To resolve these problems, the authors propose that employees should be automatically enroll.